SYMPOSIUM COMMENTARY “10th International Conference on Geographic Naming and Geographic Education”: June 28, 2019, Seoul, South Korea - Scholten, Nina (Journal of Geography Education, 2019)
As part of a five-day study visit, a delegation of thirteen American and three Euro- pean Geography teachers attended this summer a conference in South Korea organized by the Northeast Asian History Foundation (NHAF)–a think tank for Northeast Asian history research. The delegation was led by Dr. Joseph Stoltman from Western Michigan University and Siyoung Park, Professor Emerita at Western Illinois University.